Balança De Pesagem Em Movimento Para Gado Utilizando ESP32 Para Aplicações IoT (Silvano.Io) - Muniz, Caíque Veiga de Lima (Brasil, 2022)
Brazil is one of the largest beef producers in the world and the adoption of beef cattle confinement in the country has increased. However, the beef industry incessantly needs new methods, technologies and tools to meet the growing demands of the consumer market. In this context, weighing the cattle is essential so that the producer can have greater security in his decision-making, but the most used tool to have the weighing of the animals happens through a scale attached to a trunk, however, this method in addition to being risky for the animal and for those who handle it, it causes stress to the cattle, which leads to significant losses in the live weight of an animal, not to mention that stress reduces the quality of its meat, factors that cause financial losses to the rancher. . In this way, the objective of this study is to design a weighing scale in motion for cattle using ESP32 for IoT applications, developed to capture data without the need for the animal to stand still on the scale. Thus, based on experiments carried out at Fazenda Santa Rosa (AM), a scale system was developed that makes it possible to weigh animals in motion, with an LSTM neural network, without the presence of a containment trunk to force them to stop. The cattle are identified by the Radio-Frequency Identification (RFID) reader through electronic tags, and therefore, the animals have their weight recorded individually. Subsequently, the weights validated by the equipment's software are saved on an SD Card and then sent via LoRa to the gateway, which will be located at a point on the farm with internet access so that the data are available, to be shown in an application. smartphone, which needs to have internet connection and Bluetooth communication to send balance calibration data, date and time to the system. The system identifies which animal is passing over the scale, in order to collect and send to a gateway the date, weight and identification of the electronic tag, and in this way, have an individual follow-up of the animal's weight curve, without it is necessary to handle it for a common scale, avoiding risks for those who handle and losses with the loss of weight of the animal. The crossing scale achieved satisfactory results when compared with the traditional weighing method, used on the farm, with the animal immobilized in the trunk. The developed software proved to be reliable in capturing, storing and debugging data. Thus, it was concluded that the moving passage scale, developed in this study, is an efficient tool in increasing profitability and production control. Furthermore, it is an instrumentation and monitoring tool for decision making regarding productive management.